Neospora caninum Evades Immunity via Inducing Host Cell Mitophagy to Inhibit Production of Proinflammatory Cytokines in a ROS-Dependent Manner - Zhang, Xu; Wang, Yuru; Gong, Pengtao; Wang, Xiaocen; Zhang, Nan; Chen, Mengge; Wei, Ran; Zhang, Xichen; Li, Xin; Li, Jianhua (Frontiers in Immunology, 2022)
Neospora caninum is an intracellular protozoan that mainly infects cattle to cause abortion and significant economic losses worldwide. A better understanding of the immune evasion mechanisms of N. caninum could help to search for an effective approach to prevent and treat neosporosis. Mitophagy is used by some viruses to evade host immune surveillance. However, host cell mitophagy and its effect on N. caninum infection is unclear. In the present study, N. caninum-induced host cell mitophagy and its role in parasite infection were investigated in vitro and in vivo. Furthermore, the regulation of N. caninum-induced host cell mitophagy on the production of Reactive Oxygen Species (ROS), the secretions of proinflammatory cytokines, and the signals of p38, ERK, and Nlrp3 inflammasome were explored. Our results showed that autophagosomes and co-localization of LC3 with mitochondria were observed in N. caninum-infected macrophages. The mtDNA/nDNA ratio and the levels of mitochondrial marker proteins (Hsp60 and Tim23) were decreased with the increase of N. caninum numbers or infection time. N. caninum could induce mitophagy in brain and peritoneal lavage fluid cells of mice. Promoting mitophagy via mitophagy inducers (CCCP) could shorten survival time, decrease body weight, increase parasite load, and attenuate secretion of cytokines in N. caninum infected mice. CCCP treatment decreased the production of cytokines and Reactive Oxygen Species (ROS), and increased parasite burden in N. caninum-infected macrophages. Furthermore, CCCP or NAC (ROS inhibitor) treatment could inhibit ERK signal, Nlrp3 inflammasome, and cytokine production, while promote p38 signal in N. caninum-infected macrophages. The opposite results were obtained when using a mitophagy inhibitor (Mdivi1). Taken together, N. caninum-induced mitophagy could regulate the activations of p38, ERK, Nlrp3 inflammasome to inhibit the production of inflammatory cytokines in a ROS-dependent manner to escape host immune surveillance.